2017
DOI: 10.1177/2045125317718810
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitors in treatment-resistant psychotic depression

Abstract: Case reportMr M, a 53-year-old White man, had a 25-year history of recurrent, refractory psychotic depression (World Health Organization ICD-10 revision F33.3) that necessitated over 30 hospital admissions. Identifiable triggers were lacking and remission rarely achieved. Excepting childhood anxiety, he was well adjusted before first presentation. Drug or Alcohol misuse did not feature. Treatments of adequate dose and duration included: antidepressants from every major class, alone and in combination; lithium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In one case report, a patient was administered rivastigmine, donepezil and galantamine at various intervals as needed [354]. The patient was suffering from psychotic depression.…”
Section: The Use Of Ache Inhibitors For Mdd and Bpadmentioning
confidence: 99%
“…In one case report, a patient was administered rivastigmine, donepezil and galantamine at various intervals as needed [354]. The patient was suffering from psychotic depression.…”
Section: The Use Of Ache Inhibitors For Mdd and Bpadmentioning
confidence: 99%
“…The compound is also an antagonist of 5-HT1D, 5-HT3, and 5-HT7 receptors as well as agonist of 5-HT1A and partial agonist of 5-HT1B receptors (D'Agostino et al, 2015;Stahl, 2015). Vortioxetine also exhibit cholinergic activity that may be indicated for synucleinopathy-associated patients showing VH and affective disturbances (Smart et al, 2018).…”
Section: Other Possible Treatments For Visual Hallucinationsmentioning
confidence: 99%
“…Also, discontinuation of AChEIs that had been used in dementia treatment can be associated with adverse behavioral changes such as decreased time engaging in leisure activities (Daiello et al, 2009 ). There is also a study reporting potential improvement of depression-related negative signs with AChEIs in schizophrenia (Stryjer et al, 2004 ), and a case report found improvement in treatment-resistant psychotic depression on these drugs (Smart et al, 2018 ).…”
Section: Human Subjects Researchmentioning
confidence: 99%